Respuestas

¡La mejor respuesta!
2014-01-14T23:09:00+01:00
Tengamos en cuenta que el símbolo - cambia de signo a los términos de un paréntesis:
 -{-[-(+8-4-7)+(-3+8-2)+4]-2}=
 -{-[-8+4+7-3+8-2+4]-2}
-{-[-8+4+7-3+8-2+4]-2} = -{-[10]-2}=-{-10-2} = - {-12}=12

-5-{- [-7-(-11+9+8)+(+7+10+5)+8]+5}+4=-5-{- [-7+11-9-8+7+10+5+8]+5}+4
-5-{- [-7+11-9-8+7+10+5+8]+5}+4=-5-{- [17]+5}+4
-5-{- [17]+5}+4=-5-{-17+5}+4=-5-{-12}+4
-5-{-12}+4=-5+12+4=11

-3-{-2+[-11+4+7-(-8+7+9)+2]-3}-6=-3-{-2+[-11+4+7+8-7-9+2]-3}-6
-3-{-2+[-11+4+7+8-7-9+2]-3}-6=-3-{-2+[-6]-3}-6
-3-{-2+[-6]-3}-6=-3-{-2-6-3}-6=-3-{-11}-6=-3+11-6= 2